Retrospective, Registry-based, Cohort Investigation of Clinical Outcomes in Patients with Cutaneous Squamous Cell Carcinoma and Basal Cell Carcinoma in Finland - Samuli Tuominen; Liisa Ukkola-Vuoti; Pilvi Riihilä; Jaakko S. Knuutila; Veli-Matti Kähäri; Mariann Lassenius; Tuuli Ranki; Katariina Pousar; Lotta Vassilev; Sauli Vuoti; Kalle Mattila (Medical Journals Sweden, 2022)
Most cases of keratinocyte cancer can be treated effectively with surgery. However, survival is reduced in patients with advanced disease. This retrospective cohort study evaluated overall survival of patients with invasive keratinocyte cancers, and high-risk features for progression of the disease and mortality in Finnish patients in a real-world setting. A total of 43,143 patients with keratinocyte cancer types of basal cell carcinoma and 10,380 with cutaneous squamous cell carcinoma were identified nationwide. More detailed patient records were available for a subset of patients (basal cell carcinoma n = 5,020 and cutaneous squamous cell carcinoma n = 1,482) from a regional database. Fifty percent of patients with advanced cutaneous squamous cell carcinoma died approximately 4.5 years after diagnosis. Multivariable models suggested that risk factors for keratinocyte cancer progression were male sex, presence of comorbidities, immunosuppression, and pre-cancerous lesions, while risk factors for disease-specific mortality were advanced disease stage with immunosuppression, other malignancies, and consecutive surgical excisions. These results suggest that identifying patient and tumour factors associated with poor disease outcome could be important when determining appropriate treatment and follow-up; however, further studies are necessary.